Financial impacts of the Medicaid expansion on community health centers. (27th October 2021) - Luo, Qian; Moghtaderi, Ali; Markus, Anne; Dor, Avi
Abstract: Objective: To determine the impacts of the Medicaid expansion on revenues, costs, assets, and liabilities of federally funded community health centers. Data sources: We combined data from the Uniform Data System, Internal Revenue Service nonprofit tax returns, and county‐level characteristics from the Census Bureau. Our final dataset included 5841 center‐year observations. Study design: We used difference‐in‐differences model to estimate the fiscal impacts of the Medicaid expansion on community health centers. We employed event study models, state‐specific trend models, and placebo law tests as robustness checks. Data collection methods: Not applicable. Principal findings: On the revenue side, we found a 2.08 million relative increase ( p = 0.002) in Medicaid revenues, offset by a 0.44 million decrease ( p = 0.015) in total grants among community health centers in expansion states compared with centers in non‐expansion states. On the expenditure side, we found a large but not statistically significant 0.98 million relative increase ( p = 0.201) in total expenditures among centers in expansion states. Uncompensated care for health centers in expansion states decreased by 1.19 million ( p < 0.001) relative to their counterparts in non‐expansion states. Conclusions: Community health centers in expansion states benefited from the increased, stable revenue stream from Medicaid expansions. While Medicaid revenue increased as a result of the policy, we find no major evidence of substitution away from other revenue lines, with one notable exception (i.e., substitution away from state and local government grants). From a policy perspective, these results are encouraging as the Biden Administration starts to implement the safety‐net enhancements from the American Rescue Plan Act of 2021 and as more non‐expansion states are considering opting into Medicaid expansions. It is anticipated that these added revenue streams will help to sustain health centers in the delivery of health care services to the underserved population.